EDUKASI PENINGKATAN KUNJUNGAN KEHAMILAN DI WILAYAH KERJA PUSKESMAS SUNGAI AUR KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Sri Siswati; Yolanda Safitri; Sari Mulyani; Reni Novita; Yulia Arum Sekarini; Fauziah Hermawaty; Sulthan Alvin Faiz Bara Mentari; Rani Delfiyanti; Ebby Frivana; Arief Ramdhoni; Sari Yulanda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
Maternal mortality is an important public health issue addressed in developing countries. Thecause of maternal death is caused by two factors, namely direct obstetric and indirect obstetric causes. In accordance with the 2020 Puskesmas Aur Performance Assessment (PKP), it shows that the K1 target is 93% and K4 is 85% while the achievement of K1 is only 79.3% and K4 is only 50.2%.Direct causes such as medical factors can be ascertained such as bleeding, eklamsia, abnormal partus, while indirect obstetric causes of death are not easy to ascertain the cause and require special examination by medical personnel. The purpose of this activity is to increase pregnancy visits in the work area of the Sungai Aur Health Center in order to achieve the target, so that the cause of the high maternal mortality rate can be prevented. The method of this activity is to implement counseling to increase visits for pregnant women to puskesmas and meet the expected increase in targets for both K1 and K4. Continuous counselingby increasing maternal participation and awareness of the importance of pregnancy check-ups in health care facilities by health workers is carried out at puskesmas, increasing theachievement of K1 and K4. Pregnant women who need immediate help, especially when covid 19 is still ongoing, innovations are carried out by picking up patients' homes directly . The result of this activity was the implementation of counseling on the penting of pregnancy visits, and the implementation of leaflet distribution to pregnant women, as well as raising the risk of increased MMR. Counseling advice is still carried out, the readiness of manpower and means of overcoming maternal childbirth problems are preserved.